Effect of continuous white light illumination on glucosinolate metabolism during postharvest storage of broccoli. (June 2021) - Casajús, Victoria; Civello, Pedro; Martínez, Gustavo; Howe, Kevin; Fish, Tara; Yang, Yong; Thannhauser, Theodore; Li, Li; Gómez Lobato, María
Abstract: Broccoli is a vegetable consumed globally due to its important nutritional properties, including high concentrations of glucosinolates. Light treatment can be an important tool to delay postharvest senescence. In this work it was evaluated the effect of postharvest continuous white light illumination on glucosinolate metabolism of broccoli heads. Five glucosinolates were identified, one aliphatic (glucoraphanin) and four indolics (glucobrassicin, neoglucobrassicin, 4-methoxyglucobrassicin and 4-hydroxyglucobrassicin). Level of total glucosinolates decreased from 10.1 μmol/g dry tissue to 1.4 μmol/g dry tissue in control samples after five days of storage, while the decrement was only until 3.0 μmol/g dry tissue in treated samples. The expression of genes associated with glucosinolate metabolism decreased during the first three days but this decrease was greater in illuminated samples. After five days, treated samples showed a higher expression (more than twice) in most of these genes with respect to the controls, coinciding with the higher glucosinolate content. Storage of broccoli heads under continuous white light allows to keep higher values of glucosinolate contents while maintaining at the same time the visual quality. Highlights: Light treatment delays yellowing and chlorophyll degradation during broccoli storage. White light diminishes glucosinolate losses during postharvest storage of broccoli. Light enhances the expression of glucosinolates pathway genes after five days.